Two meals a day cookbook : over 100 recipes to lose weight & feel great without hunger or cravings - Sisson, Mark, 1953-; Kearns, Brad, 1965-; Steffens, Sarah (Cook) (Balance, 2022)
"Mark Sisson--author of the bestseller The Primal Blueprint and forefather of the ancestral health movement--unveiled his groundbreaking new lifestyle approach in Two Meals A Day, showing readers how to master their metabolic flexibility and reap the incredible benefits of intermittent fasting. Now, in the TWO MEALS A DAY COOKBOOK, Sisson will help you implement this eating style with nourishing recipes and a plan that is easy to adhere to for a lifetime"--